The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/mti3040071
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Order and Historical Body Shaping Children’s Making Projects—A Literature Review

Abstract: The importance of familiarizing children with the Maker Movement, Makerspaces and Maker mindset has been acknowledged. In this literature review, we examine the complex social action of children, aged from 7 to 17 (K-12), engaging in technology Making activities as it is seen in the extant literature. The included papers contain empirical data from actual digital Making workshops and diverse research projects with children, conducted in both formal and non-formal/informal settings, such as schools or museums, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 76 publications
(246 reference statements)
0
8
0
Order By: Relevance
“…mathematics classrooms (Nemirovsky, Rasmussen, Sweeney, & Wawro, 2012); astronomy (Azevedo & Mann, 2017)), it has not typically foregrounded the history or genesis of the relationships within the focal interaction. In a recent review of literature on children's making, Norouzi, Kinnula, and Iivari (2019) similarly found that histories of participants and the interactions between them are very rarely the focus of existing studies. We have found these interactional histories to be consequential to the ways embodied actions unfold and to the kinds of relations enacted within a setting over time.…”
mentioning
confidence: 99%
“…mathematics classrooms (Nemirovsky, Rasmussen, Sweeney, & Wawro, 2012); astronomy (Azevedo & Mann, 2017)), it has not typically foregrounded the history or genesis of the relationships within the focal interaction. In a recent review of literature on children's making, Norouzi, Kinnula, and Iivari (2019) similarly found that histories of participants and the interactions between them are very rarely the focus of existing studies. We have found these interactional histories to be consequential to the ways embodied actions unfold and to the kinds of relations enacted within a setting over time.…”
mentioning
confidence: 99%
“…Schools welcome opportunities to participate in projects organised in partnership with the university within these cross-subject modules as they are a new element in Finnish basic education considering their compulsory status in recent curricula (Finnish National Board of Education 2016). Conducting Making projects within and beyond schools inherently involves collaboration between participants with di erent disciplinary backgrounds (e.g., Norouzi et al 2019). Such projects thus provide fruitful possibilities to study interdisciplinary work from the perspective of the involved researchers or from the viewpoint of collaboration between di erent disciplines.…”
Section: Background For the Studymentioning
confidence: 99%
“…However, studies that combine entrepreneurship education with digital fabrication and making are scarce [35,36], even if both entrepreneurship education and digital fabrication and making have been widely studied separately. Studies on digital fabrication and making tend also to focus on success stories rather than on scrutinizing the challenges involved [25]. We aim to fill these gaps, asking as our research question, What are the challenges involved in combining digital fabrication with entrepreneurship education in the school context?…”
Section: Introductionmentioning
confidence: 99%
“…We believe they will be of use to the diverse group of researchers and practitioners coming together in Fab Labs and makerspaces, in and out of school environment, to work with children with an interest to encourage children to adopt the Protagonist role. Prior literature has shown the practitioners form a very diverse group concerning their experience and expertise, some lacking experience in pedagogy, others having very limited background in technology and making [23][24][25]28]. Hence, we expect discussion about potential challenges and associated lessons learned to be valuable.…”
Section: Introductionmentioning
confidence: 99%